(untitled) (مجلة الرازي الطبية, 2025)
In this paper, we consider a system of ecological environmental application by modeling the process of wastewater treatment. The model describes a continuously well-stirred tank containing microorganisms that degrade any degradable solid material (later referred to as the substrate). This paper discusses and illustrates the time and the concentration of the material we used, those we need to succeed this process, by studying the evolution and behavior of the system of equations to get some conditions that are necessary to treat wastewater biologically.